The Strategy of Unpar Student in Using Social Media as Part of Critical Digital Citizenship - Napitupulu, Nadya Abigail; Haya, Jihan Fadia; Angelivia, Nathania Vanessa; Angelivia, Nathania Vanessa Angelivia (Sapientia Humana: Jurnal Sosial Humaniora, 2023)
Media literacy in modern times has become a fundamental need required to be owned by the community, especially students. Through the application of good and wise media literacy, readers can avoid bad influences due to inaccurate information. In its application, media literacy has a lot of contact with social media (a digital platform that is often used for social interaction as well as a reference for exchanging information). Many cases and violations have occurred as a result of misuse of information and the spread of fake news in the digital world, for this reason, high awareness is needed for social media users to apply ethics and morals as formed in the concept of Digital Citizenship. Through globalization theory which can provide direction regarding the relationship of the three important points (media literacy, social media and digital citizenship), it is hoped that this research report can add new insights and points of view for readers. In an effort to get mature conclusions, accurate data is needed, where in this research report the related group has approached students majoring in International Relations at Parahyangan University as the target respondents to fill in the questions given through a questionnaire form. Furthermore, the analysis is created in accordance with existing data and is not contrived